Behavior of strip footing on reinforced sand slope - Altalhe, Enas B.; Taha, Mohd Raihan; Abdrabbo, Fathi M. (Journal of Civil Engineering and Management, 2015)
This study evaluated the effects of single, double, and triple reinforcing layers on the bearing capacity ratio (BCR) of strip footing on a sand slope system. Seventy-two laboratory-loading tests were conducted on a stripfooting model on a reinforced sand slope. Moreover, this study illustrated the effects of the different parameters of two reinforcing layers on the bearing capacity of a double-reinforced sand slope. The BCR increased from 1.06 to 3.00 for single-reinforced slope soils, 1.09 to 7.73 for double-reinforced slope soils, and up to 8.00 for three-layered reinforced systems. For double-reinforced soil slopes, the most effective spacing between the two reinforcing layers is 0.3 B.